Strafferettslig utilregnelighet: En diskusjon om relasjonen mellom jus og psykiatri i Norge og på Island - Gröning, Linda; Bragadóttir, Ragnheiður (Nordisk Tidsskrift for Kriminalvidenskab, 2026)
Abstract Most jurisdictions have rules and doctrines that identify defendants who, due to their mental state at the time of the act, are not accountable for their otherwise criminalised actions. Mental disorders and disabilities are, in this regard, relevant to criminal unaccountability (cf. criminal insanity) across jurisdictions. This article addresses the regulation of criminal unaccountability in Norway and Iceland and discusses how unaccountability is associated with psychiatric notions of mental disorder in legal practice. The article illuminates how the provisions on criminal unaccountability, and their implementation in practice, differ considerably between Norway and Iceland. The Icelandic provisions have remained unchanged since 1940, whereas the Norwegian provisions were introduced in 2020. There are few Icelandic academic texts on the subject, but many judgements. In Norway, it is the opposite: there are few judgements since the law reform in 2020, but a relatively large body of writing on the provisions. According to Icelandic criminal law, there must be a causal link between defendants mental state(s) and their criminal actions, whereas Norwegian law does not require a causal connection. Nevertheless, similar conditions are considered relevant to criminal unaccountability in both countries. This said, there are significant differences regarding the role of experts, which is more extensively regulated in Norway than in Iceland. Courts in both countries seem to rely on experts in similar ways and emphasise comparable normative arguments for criminal unaccountability. As such, the article reveals interesting tensions between psychiatric and legal aspects of the issue, warranting further comparative research. Title in English: Criminal unaccountability: The relationship between law and psychiatry in Norway and Iceland